2006
DOI: 10.1111/j.1369-1600.2006.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL STUDY: Alcohol administration acutely inhibits ghrelin secretion in an experiment involving psychosocial stress

Abstract: The appetite-regulating hormones leptin and ghrelin are altered in alcoholism and influence the hypothalamic-pituitary-adrenal system. We investigated whether acute ethanol ingestion and stress exposure affect ghrelin secretion. Nine healthy male volunteers were exposed to a standardized laboratory stressor involving public speaking on 2 days. On the first day they ingested 0.6 g/kg ethanol and on the second a placebo drink 50 minutes before the stressor. Plasma ghrelin, cortisol, glucose, and insulin were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 22 publications
2
65
4
3
Order By: Relevance
“…Together, these studies suggest that ghrelin levels are decreased in active drinkers and are increase during abstinence. Consistently, acute alcohol consumption suppresses plasma ghrelin levels in healthy controls (Calissendorff et al, 2005;Zimmermann et al, 2007). This suggests a possible role of this gut-brain peptide in alcohol-seeking behavior.…”
Section: Discussionmentioning
confidence: 57%
“…Together, these studies suggest that ghrelin levels are decreased in active drinkers and are increase during abstinence. Consistently, acute alcohol consumption suppresses plasma ghrelin levels in healthy controls (Calissendorff et al, 2005;Zimmermann et al, 2007). This suggests a possible role of this gut-brain peptide in alcohol-seeking behavior.…”
Section: Discussionmentioning
confidence: 57%
“…In human genetic studies a ghrelin gene haplotype has been associated with paternal heredity of alcohol-use disorder (Landgren et al 2010) and with increased weight in alcohol dependent individuals (Landgren et al 2008). After drinking alcohol the plasma levels of ghrelin decrease in healthy controls (Calissendorff et al 2005;Calissendorff et al 2006;Zimmermann et al 2007) which is a similar effect to the reduced plasma levels of ghrelin post-prandially (Tschöp et al 2001). The relationship between plasma ghrelin levels and alcohol dependence in humans is somewhat unclear, where some studies show increased whereas some show decreased levels of ghrelin (Addolorato et al 2006;Badaoui et al 2008;Hillemacher et al 2007;Kim et al 2005;Kraus et al 2005).…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 86%
“…A speculative explanation may be that the elevated peripheral ghrelin levels observed in craving alcoholics indirectly reflect the central ghrelin levels of those patients. It has also been found that the plasma levels of ghrelin are lower in active drinking alcoholics than in healthy controls (Addolorato et al., 2006; Badaoui et al., 2008; Calissendorff et al., 2006), which in all probability may be due to that acute alcohol intake reduces the plasma levels of ghrelin (Zimmermann et al., 2007). The possibility should therefore be considered that NOX‐B11‐2 did not affect alcohol intake in our rats since they were actively drinking and therefore may have had low plasma levels of ghrelin.…”
Section: Discussionmentioning
confidence: 99%